Volume 1: Development and Characterization of Multifunctional Materials; Mechanics and Behavior of Active Materials; Bioinspire 2017
DOI: 10.1115/smasis2017-3915
|View full text |Cite
|
Sign up to set email alerts
|

Study of Bioinspired Surgery Needle Advancing in Soft Tissues

Abstract: Although needle-based surgeries are considered as minimally invasive surgeries, the damage caused by the needle insertion in soft tissues, namely brain needs to be reduced. Any minor damage, swelling or bleeding in the brain tissue can lead to a long-lasting traumatic brain injury. Our approach to this challenge is to search for a proper solution in nature such as honeybees. In our previous studies, some new bioinspired needles (passive/active) mimicking honeybee stingers have been proposed and tested by condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…First, tests were performed using needles with our initial barb designs to prove the concept. Our preliminary results showed that the insertion force was decreased by 25% using barbed needles, regardless of the barb geometry and design parameter values [42][43][44][45]. These results motivated us to further study the barbs' design parameters' effects on the insertion and extraction forces.…”
Section: Methodsmentioning
confidence: 83%
“…First, tests were performed using needles with our initial barb designs to prove the concept. Our preliminary results showed that the insertion force was decreased by 25% using barbed needles, regardless of the barb geometry and design parameter values [42][43][44][45]. These results motivated us to further study the barbs' design parameters' effects on the insertion and extraction forces.…”
Section: Methodsmentioning
confidence: 83%
“…Percutaneous procedure Honeybee Free hand Sahlabadi et al [41] 2018 Percutaneous procedure Honeybee Guided Sahlabadi et al [5] 2017 Percutaneous procedure, Neurosurgery Honeybee Free hand Sahlabadi and Hutapea [14] 2018 Percutaneous procedure Honeybee Free hand Scali et al [3] 2017 Percutaneous procedure Parasitoid wasp Friction manipulation Scali et al [67] 2019 Percutaneous procedure Parasitoid wasp Friction manipulation Scali et al [12] 2017 Percutaneous procedure Parasitoid wasp Friction manipulation Schneider et al [36] 2009 Neurosurgery, Biopsy Parasitoid wasp Free hand Secoli et al [82] 2018 Percutaneous procedure Parasitoid wasp Friction manipulation Sprang et al [73] 2016 Percutaneous procedure Parasitoid wasp Friction manipulation Suzuki et al [59] 2015 Blood extraction Mosquito Friction manipulation Suzuki et al [17] 2015 Blood extraction Mosquito Friction manipulation Suzuki et al [58] 2018 Blood extraction Mosquito Friction manipulation Suzuki et al [4] 2015 Blood extraction Mosquito Friction manipulation Suzuki et al [66] 2020 Puncture Mosquito Guided Tran et al [60] 2019 Percutaneous procedure Honeybee Free hand Tsuchiya et al [95] 2004 Blood extraction Mosquito Guided Tsuchiya et al [61] 2007 Blood extraction Mosquito Guided Velivela et al [62] 2021 Wound healing Kingfisher, Porcupine Free hand Virdyawan et al [83] 2018 Percutaneous procedure Parasitoid wasp Friction manipulation Virdyawan and Y Baena [84] 2018…”
Section: Author Publication Year Medical Application Bioinspiration C...mentioning
confidence: 99%
“…This can be problematic for the surgeon in terms of accurately reaching a target, but it can also cause tissue damage resulting in pain and fear for the patient [4]. In the brain, it can lead to serious consequences such as swelling and bleeding [5]. MN patches are less invasive than hypodermic needles due to their shallow penetration depth and small diameter.…”
Section: Introduction 1background Information 11bioinspired Medical N...mentioning
confidence: 99%